A Wilkie Collins songbook - Berger, Francesco 1834-1933; Glover, Charles William 1806-1863; Coote, Charles 1831-1916; Rodwell, G. Herbert 1800-1852; Cooke, Thomas Simpson 1782-1848; Foster, Stephen Collins 1826-1864; Dibdin, Charles 1745-1814; Arkwright, Frances 1787-1849; Davy, John 1763-1824; Braham, John 1777-1856; Bishop, Henry Rowley 1786-1855 (A-R Editions, Inc., 2023)
"A Wilkie Collins Songbook consists of twenty-seven "everyday pieces" (three of them in two different versions each) that either appear in the novels and short stories of the Victorian author Wilkie Collins (1824-89) or were inspired by them. There is an overture for a stage production on which Collins collaborated with Charles Dickens; a number of pieces that reflect the popularity of The Woman in White (1860), which rocketed Collins to superstardom; and, forming the heart of the anthology, twenty ballads, patriotic songs, and traditional tunes that would have been well known to Collins's English (and American) readers. Among the twenty-two composers represented are: Francesco Berger (a regular at Dickens's Sunday-evening card games); the prolific Walter Burnot, whose business card read "Songs Written While You Wait"; Charles Dibdin, and John Davy, as well as four women: Frances Arkwright, Clara Angela Macirone, Virtue Millard, and the mysterious American called "The Veiled Lady." In all, the songbook provides an informative and entertaining romp through the everyday music of "Wilkie's World.""
Songs chiefly for 1-4 voices and piano; some for piano alone, some for fiddle, one for cornet and piano
Historical and editorial notes on pages ix-xiv
Keywords: Collins, Wilkie / 1824-1889 / Influence; Collins, Wilkie / 1824-1889 / Sources; Songs with piano / Scores and parts; Popular music / England / 19th century / Scores and parts; Popular music / United States / 19th century / Scores and parts; Songs; Popular music; Scores; Chamber music